High doses of immunoglobulin g in the therapy for severe forms of myasthenia gravis and Guillain-Barré syndrome - Lavrnić Dragana; Romić Marija; Kačar Aleksandra; Rakočević-Stojanović Vidosava; Stević Zorica; Vujić Ana; Basta Ivana; Marjanović Ivan; Bogdanović Gradimir; Apostolski Slobodan (Vojnosanitetski Pregled)
Background/Aim. High doses of immunoglobulin G (IVIG) have been recognized as a very important therapeutic modality in the treatment of neurological diseases. The aim of this report was to present our experience in the treatment of severe forms of myasthenia gravis (MG) and Guillain-Barré syndrome (GBS). Methods. We analyzed the efficacy and safety of immunoglobulin G therapy in 53 patients with severe forms of myasthenia gravis, and 27 patients with very severe forms of Guillain-Barré syndrome. Results. At the end of the follow-up period, a significant improvement was noticed in 47 out of 53 patients with myasthenia gravis ( 88.7%). In the group of 27 patients with severe forms of Guillain-Barré syndrome an improvement was registered in 19 patients (70.3%). The side effects of this therapy were mostly mild, manifested as headache, myalgia, skin rash, adynamia, and other clinically insignificant effects. No severe side effects were recognized. Conclusions. Our study clearly demonstrated the high efficacy of IVIG therapy in the treatment of severe forms of myastehnia gravis and Guillain-Barré syndrome.